Effect of surface Lewis acidity on selective catalytic reduction of NO by C3H6 over calcined hydrotalcite - Yuan, D.; Li, Xin Yong; Zhao, Q.; Zhao, J.; Liu, Shaomin; Tade, Moses (Elsevier B.V., 2013)
The selective catalytic reduction (SCR) of NO by C3H6 has been studied over a series of calcined hydrotalcite, which were prepared by four different methods to obtain various Lewis acid sites. The catalysts have been investigated by X-ray powder diffractometer, N2 adsorption, Temperature-programmed desorption of NH3 (NH3-TPD), pyridine adsorption FTIR (Py-FTIR), Temperature-programmed desorption of NO + O2 (NO + O2-TPD) and in situ FTIR techniques. The Lewis acid sites could be changed with the transformation of the crystalline structure from the mixed oxides of MgO and Al2O3 to spinel phase. It is demonstrated that Lewis acid sites play an important role in determining the catalytic performance of SCR by C3H6 over calcined hydrotalcite catalysts. Various nitrate species as the key intermediate species for SCR could form at Lewis acid sites during the process of the reaction under lean-burn condition.